Assessing provincial inter-provincial carbon flow and economic inequality in China's construction industry - Guo Xiaomin; Fang Chuanglin (Environmental and Sustainability Indicators)
Inter-regional trade leads not only to the movement of goods and economies, but also to the shifting of emissions. As one of the largest emitters in China, the carbon flow and economic inequality in the construction industry due to inter-provincial trade need to be further investigated, which is essential for developing sustainable models. Based on various data sources, this study applied the emission coefficient method, multi-regional input-output analysis, and carbon inequality index to investigate the inter-provincial transfer of carbon emissions within China's construction industry. This study found, there are substantial disparities in the embodied flows of carbon emissions and the economic benefits across provinces, with a high concentration of emissions in the northern coastal regions. Henan stands out as the province with the highest carbon emissions supporting its own development, with 172.09 × 104 t and importing the largest economic benefit,5732.89 billion yuan,. Zhejiang is the biggest contributor, of 40.92 × 104 t and 969.30 billion yuan, respectively. Additionally, the study reveals a significant correlation between net carbon emissions transfer and GDP per capita. Regions in the southeast and northeast generate higher economic output per unit of carbon emissions from the Construction Industry, in contrast to the northwest and southwest, where severe carbon inequality persists. These results highlight the need for reductions in embodied carbon emissions within the construction Industry and the implementation of carbon compensation mechanisms. This study can also serve as a reference for other emerging nations confronting similar challenges of carbon inequality and the pursuit of sustainable regional development models.